1983
DOI: 10.1111/j.1471-4159.1983.tb08058.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine and Glucose as Precursors of Transmitter Amino Acids: Ex Vivo Studies

Abstract: Radiolabelled glutamine and glucose were infused into lateral ventricles of rats in order to label transmitter amino acid pools in vivo. Brain regions close to the lateral ventricle (hippocampus, corpus striatum, hypothalamus) were labelled more effectively than more distant structures such as cerebral cortex or cerebellum. All regions were labelled to much the same extent over 30-150 min by [U-14C]glucose, [U-14C]glutamine, or [3H]glutamine administered alone or together in double-label experiments when allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(74 citation statements)
references
References 12 publications
6
68
0
Order By: Relevance
“…As reported in the Introduction, a large body of experimental data obtained by a variety of methods supports the notion that PAG is a crucial although not exclusive enzyme for the synthesis of transmitter Glu (Ji et al, 1991;Sherman and Mott, 1986;Thanki et al, 1983;Ward et al, 1983;Reubi, 1980;Hamberger et al, 1979a,b;Hertz, 1979;Bradford et al, 1978Bradford et al, ,1983. These data have been recently confirmed by showing an elevation of KCI-and 4-aminopyridine-induced Glu release from synaptosomal preparations pre-incubated with glutamine (Sherman, 1991).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…As reported in the Introduction, a large body of experimental data obtained by a variety of methods supports the notion that PAG is a crucial although not exclusive enzyme for the synthesis of transmitter Glu (Ji et al, 1991;Sherman and Mott, 1986;Thanki et al, 1983;Ward et al, 1983;Reubi, 1980;Hamberger et al, 1979a,b;Hertz, 1979;Bradford et al, 1978Bradford et al, ,1983. These data have been recently confirmed by showing an elevation of KCI-and 4-aminopyridine-induced Glu release from synaptosomal preparations pre-incubated with glutamine (Sherman, 1991).…”
Section: Discussionmentioning
confidence: 77%
“…Whether the fraction of PAG-dependent Glu immunoreactivity that is critical for immunocytochemical visualization is produced via "perikaryal" or "synaptosomal" PAG (Aoki et al, 1991) is at present completely unknown, as is the possible role of eventual perikaryal high-affinity uptake sites. Whatever the mechanism(s) responsible for cell body staining, given the crucial role of PAG in the formation of "releasable" Glu Ui et al, 1991;Sherman and Mott, 1986;Thanki et al, 1983;Ward et al, 1983;Reubi, 1980;Hamberger et al, 1979a,b;Hertz, 1979;Bradford et al, 1978Bradford et al, ,1983, the results reported here give some strength to the hypothesis that, under our experimental conditions, Glu immunoreactivity in perikarya of cortical neurons might reflect the neurotransmitter pool of Glu (i.e., that Glu immunoreactivity in cell bodies might indeed be a marker of cortical neurons releasing Glu at their nerve terminals). In the cerebral cortex, this possibility is supported by the following observations: (a) the selectivity of staining, both at light and at electron microscopic levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, this interpretation is weakened by the fact that glial-derived glutamine is not the only source of the neurotransmitter glutamate, as it can also be synthesized from glucose in neurons (Ward et al, 1983). Furthermore, the highly variable rate and degree of synaptic depression observed in different studies (from 30 mins to 5 h and from total suppression to only 85%; BergJohnsen et al, 1993;Keyser and Pellmar, 1994;Largo et al, 1996;Martin et al, 2007) raise some doubt whether the lack of transmitter is the main cause of synaptic failure during glial poisoning.…”
Section: Mechanisms Of Synaptic Blockagementioning
confidence: 99%
“…Results from metabolic labeling experiments showed that glutamine is used preferentially over glucose as the precursor for depolarization-releasable glutamate in brain slice and synaptosomal preparations (Bradford et al, 1978;Hamberger et al, 1979a,b;Ward et al, 1983). A phosphateactivated glutaminase (PAG; EC 3.5.1.2) hydrolyzes glutamine to glutamate and ammonia in the mitochondria of glutamatergic neurons (Kvamme, 1983;Erecinska and Silver, 1990;Fonnum, 1993).…”
Section: Eat-4 Is Involved Specifically In the Synaptic Function Of Gmentioning
confidence: 99%